Servant Leadership: developing a new generation of servant leaders through arts - Barroca, Ana (Conferência - Investigação e Intervenção em Recursos Humanos, 2016)
The word is in turmoil. Globalization, technology, profound demographic changes, financial crisis, ethic dilemmas lead us to question the validity of our educational and management paradigms. The new generations arriving to the workforce have different expectations and demand for more ethical, people-centered management. The future leaders are growing - socially, politically and economically - in the digital era and through a profound social, financial and economic crisis. These future leaders demand for purpose, meaning and connection and they will be working in organizations also shaped by the globalization of knowledge, markets and customers and the information and communication technology.People management and leadership will be key leverages for Europe to assert in the global context and to take a strategic role as a knowledge based economy and an innovation space. Research has been showing that the traditional management and leadership paradigms are no longer answering the current challenges that organizations are facing and are not being able to answer the expectations and needs of the new generations. “With such changes have come new priorities and responsibilities and it is in this environment that the theory of servant leadership has flourished as a management style for the redefined business world of today, one that can serve as a cornerstone for organisations wishing to build corporate structures based on stewardship, empowerment and trust.”Dirk van Dierendonck, RSM Insight 3rd Quarter, 2011 In order to deploy new learning contents and training activities about a new leadership paradigm, one must be also prepared to answer to the learning challenges posed by a generation of active learners, digital natives and graphically/visually oriented. The main goal of the Artful Leadership project is to create innovative digital learning resources about Servant Leadership, supported by arts-based learning methods and deployed through different methods and techniques (e.g. digital storytelling, visual art, design thinking, etc.).